Electron Density in Io's Alfvén Wing Observed Via Radio Occultation With Juno - D. R. Buccino; A. Caruso; D. Coffin; L. Gomez‐Casajus; M. Parisi; M. Zannoni; E. Gramigna; P. Withers; P. Tortora; R. S. Park; P. Steffes; S. Bolton (Geophysical Research Letters)
Abstract Juno performed close flybys of the innermost Galilean moon, Io, in December 2023 (I57) and February 2024 (I58). During these flybys, the radio link connecting the Juno spacecraft to Earth observing stations of NASA's Deep Space Network (DSN) propagated through the Alfvén wing, a magnetospheric feature in which plasma is produced between Io and Jupiter. The radio link is sensitive to the elevated electron densities in the Alfvén wing. A direct measurement of the total electron content was made by a linear combination of Juno's X‐band and Ka‐band downlink frequencies. Two different approaches were used in inverting the measurements into electron densities which assume different electron density distributions within the Alfvén wing. The maximum electron densities estimated in the Alfvén wing were 20,500–27,000 cm−3 on I57, in the northern Alfvén wing, and 15,300–31,000 cm−3 on I58, in the southern Alfvén wing.